Studi Faktor yang Mempengaruhi Keputusan Pasangan Usia Subur dalam Menggunakan KB Implan - Dian Zuiatna; Suyanti Suwardi (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
According to Government Regulation of the Republic of Indonesia Number 87 of 2014 concerning population development and family development, family planning and family information systems. The family planning (KB) program is a program that seeks to regulate childbearing, spacing and ideal age of birth, manage pregnancy, through the promotion of protection and assistance in accordance with reproductive rights to create a quality family. Many couples of childbearing age still have limited knowledge about implant contraception, including how it works, benefits, side effects, and its safety as a long-term contraceptive method. This results in low interest and trust in the use of implant contraception. The purpose of this study is to determine the factors that influence the decision of fertile couples in using implant contraception. This type of research uses a survey method with a cross-sectional approach, namely where measurements or observations are carried out simultaneously on the independent and dependent variable data. The population is all PUS mothers who use implant contraception in Bandar Khalifah Village, namely 45 people by total sampling. Data analysis uses the chi-square test and multivariate with logistic regression tests. Based on the results of the logistic regression test, this study shows that there is an influence of knowledge on implant contraception in Bandar Khalifah Village, Percut Sei Tuan District, Deli Serdang Regency with an Exp (B) value of 103.964. The conclusion of this study is that the variable of knowledge is the most influential factor on the use of contraceptive implants in PUS in Bandar Khalifah Village. Therefore, health workers should provide counseling and promotion to the community, especially in PUS, about contraceptive implants so that the community's knowledge and attitudes become better. The results of this study can be a basis for health workers, especially midwives and family planning officers, in developing more effective and targeted educational, counseling, and approach strategies to increase the use of contraceptive implants.